EDUKASI BAHAYA ROKOK SEJAK DINI PADA SISWA SEKOLAH DASAR di SDN PEULANTEU KECAMATN BUBON KABUPATEN ACEH BARAT - Kusumawardani, Eva; Syam, Nasrianti; Paradhiba, Meutia; Harahap, Laila Apriani Hasanah; Ernawati; Rimonda, Rubi; Fadillah, Mardi; Putra, Onetusfifsi; Saputra, Firman Firdauz; Siahaan, Perry Boy Chandra (Fakultas Teknik, Universitas Samudra, 2024)
The prevalence of smoking among school-aged adolescents, specifically those aged 10–18 years, increased according to the 2018 Basic Health Research (Riskesdas) report. Youth smoking remains a serious public health issue despite various prevention and reduction efforts implemented in many countries, including Indonesia. The aim of educating sixth-grade students at SDN Peulanteu about the dangers of smoking was to enhance their knowledge regarding the risks of smoking for both active and passive smokers. The method used in this community service activity was health education, which included lectures and discussions. The material was delivered by lecturers and students from Teuku Umar University using media such as PowerPoint presentations and leaflets. Additionally, question-and-answer sessions and ice-breaking activities were conducted to increase interaction with participants. This community service activity successfully improved students' understanding of the health risks associated with smoking. The educational sessions fostered enthusiasm among students in grasping the presented material. It is recommended that health workers and educators continue to conduct regular awareness campaigns on the dangers of smoking to strengthen students' understanding. Furthermore, developing more engaging and interactive educational materials, such as digital media or educational games, is suggested to capture students' attention effectively.